Return to sports for adolescents and children after recovery from COVID-19 - Chowdhury, D.; Briskin, S.; Snyder, C. S. (Contemporary Pediatrics, 2021)
Coronavirus 2019 disease (COVID-19) is often mild, but can lead to cardiovascular harm. Ensuring the safe return to sports by affected children will be a necessity.